Hospitalized Pets as a Source of Carbapenem-Resistance - Gentilini, Fabio; Turba, Maria Elena; Pasquali, Frederique; Mion, Domenico; Romagnoli, Noemi; Zambon, Elisa; Terni, Daniele; Peirano, Gisele; Pitout, Johann Dawid Daniel; Parisi, Antonio; Sambri, Vittorio; Zanoni, Renato Giulio (Frontiers in Microbiology, 2018)
The massive and irrational use of antibiotics in livestock productions has fostered the occurrence and spread of resistance to “old class antimicrobials”. To cope with that phenomenon, some regulations have been already enforced in the member states of the European Union. However, a role of livestock animals in the relatively recent alerts on the rapid worldwide increase of resistance to last-choice antimicrobials as carbapenems is very unlikely. Conversely, these antimicrobials are increasingly administered in veterinary hospitals whose role in spreading bacteria or mobile genetic elements has not adequately been addressed so far. A cross-sectional study was carried out on 105 hospitalized and 100 non-hospitalized pets with the aim of measuring the prevalence of carbapenem-resistant Gram-negative bacteria colonizing dogs and cats, either hospitalized or not hospitalized and estimating the relative odds. Stool samples were inoculated on MacConkey agar plates containing 1 mg/L imipenem which were then incubated aerobically at 37°C 1 for 48 h. Isolated bacteria were identified first by Matrix-assisted laser desorption/ionization time-of-flight mass spectrometry and were confirmed by 16S rRNA sequencing. The genetic basis of resistance was investigated using PCR methods, gene or whole genome sequencing. The prevalence of pets harboring carbapenem-resistant bacteria was 11.4%, and 1.0% in hospitalized and not-hospitalized animals, respectively, with an odds ratio of 12.8 (p<0.01). One pet carried two diverse isolates. Overall, 14 gram-negative non-fermenting bacteria, specifically, one Acinetobacter radioresistens, five Acinetobacter baumannii, six Pseudomonas aeruginosa and two Stenotrophomonas maltophilia were isolated. The Acinetobacter species carried acquired carbapenemases genes encoded by blaNDM-1 and blaOXA-23. In contrast, Pseudomonas phenotypic resistance was associated with the presence of mutations in the oprD gene. Notably, inherent carbapenem-resistant isolates of S. maltophilia were also resistant to the first-line recommended chemotherapeutic trimethoprim/sulfamethoxazole. This study estimates the risk of colonization by carbapenem-resistant non-fermenting gram-negative bacteria in pets hospitalized in veterinary tertiary care centers and highlights their potential role in spreading resistance genes among the animal and human community. Public health authorities should consider extending surveillance systems and putting the release of critical antibiotics under more strict control in order to manage the infection/colonization of pets in veterinary settings.